Predictive and Prognostic Role of Tumor-Infiltrating Lymphocytes for Early Breast Cancer According to Disease Subtypes: Sensitivity Analysis of Randomized Trials in Adjuvant and Neoadjuvant Setting. (10th February 2016) - Carbognin, Luisa; Pilotto, Sara; Nortilli, Rolando; Brunelli, Matteo; Nottegar, Alessia; Sperduti, Isabella; Giannarelli, Diana; Bria, Emilio; Tortora, Giampaolo
Abstract: Background: The role of tumor-infiltrating lymphocytes (TILs) in breast cancer (BC) is still an issue for clinical research. Toward this end, a sensitivity analysis of neoadjuvant and adjuvant randomized clinical trials was performed according to disease subtypes. Methods: Pathological complete responses (pCRs) after neoadjuvant treatment according to the presence or absence of lymphocyte-predominant BC (LPBC) were extracted and cumulated as odds ratios (ORs) by adopting a random-effects model by subtype. Overall survival hazard ratios as a function of 10% incremental values of stromal TILs (sTILs) in adjuvant trials were extracted. The interaction test was adopted to determine the differential effect according to the subtype. Results: Eight trials (5, 514 patients) were identified. With regard to neoadjuvant setting (4 studies), a significant interaction ( p < .0001) according to LPBC was found. The presence of LPBC was associated with a 29.5% increase in pCR rate compared with non-LPBC ( p < .0001). The pCR rate was significantly higher in patients with LPBC in triple-negative BC (TNBC) and HER2-positive BC settings, with an absolute difference of 15.7% (95% confidence interval [CI], 4.9%–26.2%) and 33.3% (95% CI, 23.6%–42.7%), respectively. With respect to the adjuvant setting (4 studies), a significant interaction ( p < .0001) according to sTILs was found. A survival benefit was more likely to be determined for HER2-positive BC ( p = .025) and TNBC ( p < .0001), with no statistically significant difference for estrogen receptor-positive/HER2-negative disease. Conclusion: Despite the retrospective nature of this analysis, the presence of TILs may represent a robust predictive and prognostic marker for BC, particularly for TNBC and HER2-positive disease. Abstract : The presence of tumor-infiltrating lymphocytes may potentially be a robust predictive and prognostic marker for breast cancer, particularly for triple-negative breast cancer and HER2-positive disease.